Amount and isolation of aquatic habitat drive anuran diversity in agricultural landscapes in the Brazilian Cerrado - Silveira, Priscila; Iop, Samanta; dos Santos, Juliana Silveira [UNESP]; Lima, Edgar L.; Martello, Felipe; Ribeiro, Milton Cezar [UNESP]; Maciel, Natan M.; Collevatti, Rosane G. [UNESP] (Springer Nature, 2023)
Context: Declining in biodiversity in the Anthropocene is mostly a result of habitat loss due to changes in the landscape. Objectives: Here, we address how landscape composition and configuration affect anuran diversity in agricultural landscapes in the Brazilian Cerrado ecoregion. Methods: We sampled 29 breeding sites during the rainy season using auditory census and visual encounters to record anuran species richness, and specialist, generalist and dominant species richness. For each sampling site, we estimated eight landscape metrics at five spatial scales. Results: We recorded 36 species from seven anuran families, 17 habitat specialist and 19 habitat generalists. We found that aquatic habitat cover (%) and number of aquatic patches played a positive effect on both total anuran richness and richness of dominant species. However, landscape compositional heterogeneity and aquatic habitat isolation negatively influenced community rarity, and abundance of habitat specialist species. In addition, more diverse anuran communities were found in areas where the amount and number of aquatic habitat patches were greater. Conclusions: Our results emphasize the importance of maintaining high amounts of waterbodies and high aquatic habitat connectivity across the landscapes. Moreover, rare species and habitat specialist species are sensitive to landscape composition and configuration, respectively. Therefore, water body amount and connectivity must be considered in conservation plans to mitigate anuran community loss in agricultural landscapes.
Keywords: Alpha diversity; Amphibian; Community structure; Landscape ecology; Savanna; Spatial scale